Komposisi Media Tanam Organik terhadap Pertumbuhan dan Produksi Jahe Merah (Zingiber officinale var. rubrum) di Polybag - Pujiasmanto, Bambang; Triharyanto, Eddy; Sulandjari, Sulandjari; Harsono, Puji; Pardono, Pardono; Widijanto, Herry; Nadhifatul Ardhina, Safira Nadhifatul; Setyaningrum, Desy (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2022)
The productivity of red ginger in Indonesia has decreased by 9,174 tons compared to 2017. The decrease is due to the very limited area of red ginger production, the method of red ginger cultivation, which is still very conventional, and the low amount of organic matter in the soil. This study examines the effect of planting media composition on the growth and production of red ginger. The study used a Completely Randomized Block Design (RCBD) with six treatments, namely control (soil without manure), cow manure: green manure: soil (1:1:1), P2 = goat manure: green manure: soil (1:1:1), green manure: soil (1:2), cow manure: soil (1:2), and goat manure: soil (1:2) and repeated four times. Composition media of goat manure: green fertilizer: soil with a ratio of 1:1:1 could increase the growth of red ginger in variable plant height, number of leaves in the clump, leaf area, and the weight of fresh stover with a yield of 52.7 cm; 10,75; 148,5; 2952.59 cm2; and 307.33 g. Composition of green fertilizer media: soil with a ratio of 1:2 could increase the weight of dry stover with a value of 39.32 g, and red ginger production includes fresh weight of rhizomes 111.32 g, storage weight of rhizomes 107.87 g, and rhizome volume 124.12 cm3.